PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMP ALAM AR-RIDHO SEMARANG - Akmal, Firdaus; Purnomo, Arif; Salam, Rudi (Universitas Negeri Semarang, 2020)
Ar-Ridho Natural Junior High School is a school that has included entrepreneurship education in its school curriculum. The objectives of the study were: 1) to expost enterpreneurship education of Ar–Ridho Natural High School; 2) to study students’s enterpreneurial interest; and 3) to reveal the extent of the effect of entrepreneurship education on the emergence of entrepreneurial interest in students of Ar-Ridho Natural Junior High School Semarang. This research uses a quantitative method approach with the Expost Facto research design. The results indicate that the average value of Entrepreneurship Education at Ar-Ridho Semarang Junior High School was located at the high category, while the average value of Entrepreneurial Interest of students at the Alam Ar-Ridho Junior High School Semarang was located at the high category. The Constant Value is 16,803 which means that if the application of Entrepreneurship Education is equal to zero, then the consistent value of the variable entrepreneurship interest is 16,803. The coefficient of variable X is 1,307. The conclution of this study is the Entrepreneurship Education influences the Entrepreneurial Interest of students of Alam Ar-Ridho Semarang Junior High School. SMP Alam Ar–Ridho Semarang merupakan sekolah yang sudah memasukkan pendidikan kewirausahaan di dalam kurikulum sekolahnya. Tujuan dari penelitian ini adalah untuk: 1) mengungkap bagaimana penerapan pendidikan kewirausahaan pada siswa SMP Alam Ar–Ridho Semarang; 2) bagaimana minat berwirausaha siswa SMP Alam ArRidho Semarang; dan 3) bagaimana pengaruh pendidikan kewirausahaan terhadap munculnya minat berwirausaha siswa SMP Alam Ar–Ridho Semarang. Penelitian ini menggunakan pendekatan metode kuantitatif dengan desain penelitian Expost Facto. Hasil penelitian menunjukkan bahwa nilai rata–rata Pendidikan Kewirausahaan SMP Alam Ar–Ridho Semarang terletak pada kategori tinggi, sedangkan nilai rata–rata Minat Berwirausaha siswa SMP Alam Ar– Ridho Semarang terletak pada kategori tinggi. Nilai Konstanta adalah sebesar 16,803 mengandung arti bahwa jika penerapan Pendidikan Kewirausahaan sama dengan nol, maka nilai konsisten variabel minat berwirausaha adalah sebesar 16,803. Koefisien variabel X sebesar 1,307. Kesimpulan penelitian ini adalah Pendidikan Kewirausahaan berpengaruh terhadap Minat Berwirausaha siswa SMP Alam Ar–Ridho Semarang.